Analysis of The Influence of Seeds, Labor, and Fertilizer Use on Edamame Soybean Production at PT. Tweseven Farm Partners in Jember District - Muhammad Arifin; Endro Sugiartono (Jurnal Manajemen Agribisnis dan Agroindustri)
The aim of the research is 1.) To test and analyze the influence of production factors, namely land area, seeds, labor, and partial use of fertilizer on edamame soybean production at PT Mitra Tani Dua Tujuh. 2.) To test and analyze the influence of production factors, namely land area, seeds, labor, and simultaneous use of fertilizer on edamame soybean production at PT Mitra Tani Dua Tujuh. This research uses quantitative descriptive methods. The types of data used are primary and secondary data, data collection techniques used are interviews, observation, questionnaires and documentation. The research was conducted at one of the edamame soybean producing centers in Jember Regency, namely PT Mitra Tani Dua Tujuh. In this research, cross section data is used, namely data that describes the situation at a certain time. The number of samples taken in this research was 46 foreman farmers who worked at PT Mitra Tani Dua Tujuh. The analytical tool used in the research is regression from the Cobb-Douglas production function which is calculated using a multiple linear regression equation. The research results that can be concluded are that in partial regression testing there is a positive and significant influence between the seed variable (X2) and the labor variable (X3) on edamame soybean production while the fertilizer use variable (X 4 ) has a positive but not significant influence on Edamame soybean production. In simultaneous regression testing, there was a significant influence between the seed variables (X2), labor (X3), fertilizer use (X4) on edamame soybean production at PT Mitra Tani Dua Tujuh in Jember Regency.